Penggunaan Media Animasi Audio Visual untuk Meningkatkan Hasil Belajar IPA di SD Negeri 2 Kota Ternate - Taslim Buaja; Rahayu Ramadanaryanthi; Safri Miradj (Attractive : Innovative Education Journal, 2024)
The Study done with objective For know the use of audio visual animation media in science subjects in improving learning outcomes of class VI A students of SD Negeri 2 Kota Ternate. The type of research used is Classroom Action Research (CAR). The subjects in this study were 30 class VI A students consisting of 17 boys and 13 girls. The implementation of the action was carried out in 2 cycles and each cycle was carried out in 2 meetings. Each meeting must go through 4 stages, namely planning, implementation, observation, and reflection. After the implementation of cycle I, the students' learning outcomes with an average value of 67 or classical completeness were 16 students (53%). Furthermore, in cycle II, an average value of 77 was obtained with classical completeness of 27 students (90%). Based on the results of the study, it can be concluded that audio-visual animation media can improve science learning outcomes, especially in the material of simple electrical components in class VI-A students of SD Negeri 2 Kota Ternate